2023
DOI: 10.1111/jfb.15400
|View full text |Cite
|
Sign up to set email alerts
|

Revision of Nannocharax luapulae Boulenger, 1915 (Characiformes: Distichodontidae) from the Upper Congo basin: Evidence for a species pair

Abstract: For many decades, Nannocharax luapulae has been considered to be widespread in the southern part of the Upper Congo basin. However, meristic, morphometric and cytochrome c oxidase subunit I (COI) barcoding evidence revealed that its geographical distribution is restricted to the Luapula‐Moero basin. The populations of the Upper Lualaba are assigned to a new species, N. chochamandai. This new species, though highly similar to N. luapulae, can readily be distinguished from it by its lower number of lateral line … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…A new Nannocharax species for science has been collected in the Lovoi River [50]. This new species, here named N. sp.…”
Section: Distichodontidaementioning
confidence: 99%
See 1 more Smart Citation
“…A new Nannocharax species for science has been collected in the Lovoi River [50]. This new species, here named N. sp.…”
Section: Distichodontidaementioning
confidence: 99%
“…The main difference between these two ecoregions lies in the fish fauna of the Congo River tributaries. In addition, Chiloglanis msirii [34] and Nannocharax chochamandai [50] are reported from the UNP (Upper Lualaba) and the Lukuga River basin, the outlet of Lake Tanganyika (Upper Congo), reflecting the interchange between these two ecoregions. Finally, a Cytb mtDNA genetic study between different populations of Clarias gariepinus from the Congo Basin and its surrounding basins revealed that the population of the Kamalondo Depression (UNP, Upper Lualaba), and those of Kisangani (Upper Congo) and Kinshasa (Pool Malebo) have a high affinity [97], thus providing the phylogenetic evidence of fish connectivity between these neighbouring ecoregions within the Congo Basin.…”
Section: Ichthyofaunal Affinities With the Neighbouring Ecoregionsmentioning
confidence: 99%